The effect of social media use on body image and portion selection among NTU female undergraduates - Lim, Tiffany Jia Ying (2017)
The current study seeks to examine the effects of social media use on eating behaviors- that is, how simply spending time on social media would affect an individual’s intended eating behaviors and attitudes towards their body. This experiment, conducted on Nanyang Technological University (NTU) female undergraduates (N = 89), aimed to understand how spending time on social media (specifically Facebook) would influence an individual’s body image and subsequent intended eating behaviors, as opposed to browsing a control website (i.e. Straits Times). We found that an acute instance of browsing Facebook increases an individual’s body dissatisfaction and decreases their portion sizes they subsequently intend to consume. We further found that disruptions in body image mediated the relationship between Facebook use (vs. control) and restrained portion selection patterns. Our findings also suggest that browsing Facebook increases an individual’s personal concerns about gaining weight. Given the amount of time that young adults spend on social network sites daily and widespread use of social media globally, the potential negative effects of this increased exposure to social media should be taken into serious consideration. Practical implications, limitations and directions for future research are discussed.